Theoretic Study of Various Image Compression Techniques: A Survey - Singh, Rashmi; Agarwal, Sugandha (International Journal of Computer Sciences and Engineering, 2015)
Image compression is widely used term in digital image processing. Image compression main aim is to reduce the redundant data and retaining the important data keeping the image quality as good as possible. The compressed image is represented by less number of bits compared to original. In this paper we review and discuss about the principle of image compression, need of image compression, advantages and disadvantages of image compression, classes of compression and various algorithm of image compression. At last we define what qualities image compression algorithm should contain follows with the discussion and conclusion.